Perceived sexual harassment and gender differences in anesthesiology: a cross-sectional survey - Shenoy, Renuka; Harter, Ronald; Uribe, Alberto; Abdel-Rasoul, Mahmoud; Tishko, Jillian; Weaver, Tristan; Stein, Erica (Frontiers in Public Health, 2025)
BackgroundIn 2017, the hashtags #MeToo and #MeTooMedicine went viral and raised awareness of sexual harassment (SH) and sexual violence affecting all ages, genders, races, sexualities, and careers. Most studies investigating SH have found that women report higher rates of SH experiences compared to men, with documented incidences reaching as high as 81%. Notably, 47% of these incidents go unreported. A study from the Association of Anesthesiologists found that female victims of sexual assault often do not speak up due to the myth that harassment is rare, which further silences women and stigmatizes this issue, leading them to be discouraged from participating in academic anesthesia. Due to the outdated data examining the incidence of SH in the field of anesthesiology, an anonymous 20 item survey was administered to physician attendings and trainees to assess the incidence of SH perceiving SH within the field.MethodsAn anonymous questionnaire-based cross-sectional study, adapted from a validated survey tool on SH and burnout, was administered to a sample of registered members of the American Society of Anesthesiologists (ASA) to evaluate physicians’ perceptions related to SH and burnout in their workplace.ResultsThe email survey was sent to 30,765 registered ASA members; a total of 2,830 (9.2%) members responded to the 20-item survey for this quantitative analysis. 53.4% (n = 1,511) and 44.2% (n = 1,251) identified themselves as men and women, respectively. Among all the respondents, 57.6% perceived some form of SH (75.5% women and 44.2% men, p-value:<0.0001). Around 40.1% of respondents indicated that they did not react to or report SH events, with a significantly higher incidence among women when compared to men (46.3% vs. 35.5%; p-value:<0.0001). Respondents who perceived SH were more likely to agree with the 5-point Likert-scale questions related to experiencing burnout, facing declining job opportunities or leaving a job, and becoming more emotionally detached from others.ConclusionSH has been reported by both male and female anesthesiologists, with female physicians perceiving significantly higher rates of SH compared to their male counterparts. Most respondents who experienced SH in their workplaces expressed agreement with statements related to “burnout feelings” and/or “declining a job opportunity or leaving the workplace.” This study contributes to the current literature that SH is prevalent within the field of anesthesiology. Furthermore, our study demonstrates that SH has a positive correlation to feelings of burnout. This study demonstrates the critical importance of instituting policies regarding reporting SH events. Additionally, implementing bystander training can empower individuals to report witnessed SH events. Lastly, safeguards should be implemented to protect those who report witnessing or experiencing SH events.